2019
DOI: 10.1101/529677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutations in thyroid hormone receptor α1 cause premature neurogenesis and progenitor cell depletion in human cortical development

Abstract: Mutations in the thyroid hormone receptor α 1 gene (THRA) have recently been identified as a cause of intellectual deficit in humans. Patients present with structural abnormalities including microcephaly, reduced cerebellar volume and decreased axonal density. Here, we show that directed differentiation of THRA mutant patient-derived iPSCs to forebrain neural progenitors is markedly reduced, but mutant progenitor cells can generate deep and upper cortical layer neurons and form functional neuronal networks. Qu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In rodents, hypothyroidism affects radial glial cells (22). THRA mutations cause abnormal adhesion and proliferation of human cortical progenitors (23), suggesting alterations in the radial glia. Radial glial cells are immunoreactive for MCT8 and OATP1C1 in human fetal brain slices (9).…”
Section: Resultsmentioning
confidence: 99%
“…In rodents, hypothyroidism affects radial glial cells (22). THRA mutations cause abnormal adhesion and proliferation of human cortical progenitors (23), suggesting alterations in the radial glia. Radial glial cells are immunoreactive for MCT8 and OATP1C1 in human fetal brain slices (9).…”
Section: Resultsmentioning
confidence: 99%
“…Thyroid hormone receptor alpha mutations Two intriguing studies using novel models of thyroid hormone receptor alpha (THRA) mutations, which cause thyroid hormone resistance syndrome (RTH), were published in 2020. Krieger et al [1] demonstrated the essential actions of thyroid hormone receptor alpha (TRα) on the normal development of the human cerebral cortex. The authors previously reported that adult patients with RTH had intellectual impairments, especially affecting nonverbal IQ and delayed sensorimotor processing [2].…”
Section: New Understandings Of Thyroid Hormone Actions and Signaling Mechanismsmentioning
confidence: 99%
“…Indeed, these findings were consistent with those of a mouse model with a mutant variant of TRα1, which showed a range of central nervous system abnormalities [3], but the cellular mechanisms of the impacts of THRA (the gene encoding TRα) on neural development remained unclear. Krieger et al [1], using THRA mutant patient-derived induced pluripotent stem cell (iPS) models in combination with a quantitative lineage analysis, gene expression analysis, and novel assays of neuro-epithelium formation, showed that THRA regulates the balance between progenitor self-renewal and neurogenesis, thereby affecting the overall brain mass and especially the cortex. A structural www.e-enm.org 37 modeling study of the ligand-binding domain of TRα1 demonstrated that the THRA mutation facilitates corepressor binding.…”
Section: New Understandings Of Thyroid Hormone Actions and Signaling Mechanismsmentioning
confidence: 99%